The Role of the Principal's Transformational Leadership in Islamic Religious Education Curriculum Innovation at Panca Budi Middle School Medan - Irwanto, Ronny; Tumiran, Tumiran; Abrianto, Danny (Universitas Pahlawan Tuanku Tambusai, 2025)
The transformation of national education marked by the implementation of the Independent Curriculum has placed principals in a strategic position as leaders of change. Not only as administrators, principals are required to be the driving force of curriculum innovation, particularly in the field of Islamic Religious Education (PAI) which has unique characteristics of values and spirituality. This study aims to investigate the role of the principal's transformational leadership in initiating and implementing PAI curriculum innovation at Panca Budi Middle School, Medan. A qualitative research method with a case study approach was used to explore data in depth through interview techniques, participatory observation, and documentation. The research findings show that; (1) the principal plays an active role in developing a PAI learning vision that is contextual and relevant to current developments; (2) encouraging teachers to innovate in learning methods, and creating a collaborative culture in curriculum development. The innovations carried out include the integration of Islamic values with an active learning approach; (3) Utilization of digital technology, as well as strengthening the affective dimension and character of students. Thus, transformational leadership is a key element in presenting a new face of religious education that is humanistic, transformative, and future-oriented.